Simple inverse trigo....

Geometry Level 3

Simplify

s i n ( c o t 1 ( t a n ( c o s 1 x ) ) ) sin(cot^{-1}(tan(cos^{-1}x)))

1 1 x 2 \frac{1}{\sqrt{1-x^{2}}} x x 1 x \frac{1}{x} 0

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Nikhil Raj
Jun 4, 2017

sin ( cot 1 ( tan ( cos 1 x ) ) ) L e t , cos 1 x = θ S o , cos θ = x T h e n , sin θ = ( 1 x 2 ) T h e n , tan θ = sin θ cos θ = 1 x 2 x S o , θ = tan 1 1 x 2 x c o s 1 x = tan 1 1 x 2 x = θ . Putting this in the question , we get - A = sin ( cot 1 ( tan ( cos 1 x ) ) ) = sin ( cot 1 ( tan ( tan 1 1 x 2 x ) ) ) = sin ( cot 1 ( 1 x 2 x ) ) . . . . . . . . . . . . . . . . . . . . . . . . . . . . ( 1 ) L e t , cot 1 ( 1 x 2 x ) = ϕ S o , cot ϕ = 1 x 2 x cos ϕ sin ϕ = 1 x 2 x cos 2 ϕ sin 2 ϕ = 1 x 2 x 2 1 sin 2 ϕ sin 2 ϕ = 1 x 2 x 2 sin ϕ = x sin 1 x = ϕ sin 1 x = cot 1 ( 1 x 2 x ) = ϕ Putting this in 1, we get - A = sin ( cot 1 ( 1 x 2 x ) ) = sin ( sin x ) = x \sin(\cot^{-1}(\tan(\cos^{-1}x))) \\ Let, \cos^{-1}x = \theta \\ So, \cos \theta = x \\ Then, \sin \theta = \displaystyle \sqrt{(1 - x^2)} \\ Then, \tan \theta = \dfrac{\sin \theta}{\cos \theta} = \dfrac{\sqrt{1 - x^2}}{x} \\ So, {\theta = \tan^{-1} \dfrac{\sqrt{1 - x^2}}{x}} \\ \therefore {\color{#3D99F6}{cos^{-1}}x = \tan^{-1} \dfrac{\sqrt{1 - x^2}}{x} = \theta}. \\ {\text{Putting this in the question , we get -}} \\ A = \sin(\cot^{-1}(\tan(\cos^{-1}x))) = \sin(\cot^{-1}(\tan(\tan^{-1} \dfrac{\sqrt{1 - x^2}}{x}))) = \sin(\cot^{-1}(\dfrac{\sqrt{1 - x^2}}{x}))............................(1) \\ Let, \cot^{-1}(\dfrac{\sqrt{1 - x^2}}{x}) = \phi \\ So, \cot \phi = \dfrac{\sqrt{1 - x^2}}{x} \\ \dfrac{\cos \phi}{\sin \phi} = \dfrac{\sqrt{1 - x^2}}{x} \\ \implies \dfrac{\cos^{2} \phi}{\sin^{2} \phi} = \dfrac{1 - x^2}{x^2} \implies \dfrac{1 - \sin^2 \phi}{\sin^2 \phi} = \dfrac{1 - x^2}{x^2} \implies \sin \phi = x \implies \sin^{-1} x = \phi \\ \color{#3D99F6}{\therefore \sin^{-1} x} = \cot^{-1}(\dfrac{\sqrt{1 - x^2}}{x}) =\phi \\ {\text{Putting this in 1, we get -}} \\ A = \sin(\cot^{-1}(\dfrac{\sqrt{1 - x^2}}{x})) = \sin(\sin x) = \huge \boxed{x}

1 pending report

Vote up reports you agree with

×

Problem Loading...

Note Loading...

Set Loading...